An observer design for active suspension system - Ahmad, Adizul; Md. Sam, Yahya; Abd. Ghani, Nor Maniha (2005)
The purpose of this paper is to construct an active suspension for a quarter car model with observer design. The proportional-integral sliding mode is chosen as a control strategy, and the road profile is estimated by using an observer design. The performance of the proposed controller will be compared with the linear quadratic regulator by performing extensive computer simulation.